Il gioco mentale del lettore nel mondo stilizzato di Eva e Diabolik - Cristante, Stefano (Mediascapes journal, 2023)
This short essay intends to reflect on two elements that can help motivate Diabolik’s decades-long success: the first is the reader’s involvement in the realization of the thefts of the Diabolik-Eva Kant couple. In fact, the reader is called to participate in the preparation of the robberies which, despite all the precautions taken by the owners and the police, will be carried out by the two criminals. Diabolik’s technological superiority and ability to anticipate opponents’ moves allow him to react to any adversity, and to invariably surprise the reader, aware of the inevitable success of the enterprise even though the conditions of the narrative context seem to make it impossible every time. The second crucial element of this serial comic is stylization, understood as supreme essentiality, both in the writing of the texts and in the graphic design, and which is also reflected in the characterization of the characters. The self of the actors in the series actually appears more connected to Goffman’s sociological explorations than to psychological dynamics: it will again be up to the reader to add – in the most authentic sense of comics as a cool medium – everything that in the events of the criminal couple is only stylized, making sure that a narrative ecosystem is outlined capable of continuous imperceptible variations and of a solid permanence in the mental game defined since the beginning.